2005
DOI: 10.3748/wjg.v11.i18.2748
|View full text |Cite
|
Sign up to set email alerts
|

Drug sensitivity and drug resistance profiles of human intrahepatic cholangiocarcinoma cell lines

Abstract: Sensitivity to chemotherapeutic agents is not associated with the histological type of CCA. Choosing of the appropriate chemotherapeutic regimen for the treatment of CCA requires knowledge of drug sensitivity. MRP3 was correlated with resistance of CCA cell lines to etoposide, doxorubicin and pirarubicin, whereas other chemotherapeutic drugs showed no association. The role of this multidrug resistance-associated protein, MRP3, in chemotherapeutic resistance in CCA patients needs to be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 35 publications
1
78
1
Order By: Relevance
“…In a previous study, MRP1 and MRP3 have been reported to be highly expressed in the five human CCA cell lines, while MRP2 was only moderately expressed and MDR1 expression was detected only in one cell line. A strong correlation was also found between the level of MRP3 expression and the IC 50 values of the anticancer drugs etopocide, doxorubicin, and pirarubicin (Tepsiri et al, 2005). Consistent with this finding, a strong association between MRP3 mRNA level and response to doxorubicin has been reported in lung cancer (Young et al, 1999).…”
Section: Discussionmentioning
confidence: 56%
“…In a previous study, MRP1 and MRP3 have been reported to be highly expressed in the five human CCA cell lines, while MRP2 was only moderately expressed and MDR1 expression was detected only in one cell line. A strong correlation was also found between the level of MRP3 expression and the IC 50 values of the anticancer drugs etopocide, doxorubicin, and pirarubicin (Tepsiri et al, 2005). Consistent with this finding, a strong association between MRP3 mRNA level and response to doxorubicin has been reported in lung cancer (Young et al, 1999).…”
Section: Discussionmentioning
confidence: 56%
“…Downregulation and/or impaired activity of enzymes involved in gemcitabine and 5-fluorouracil activation, such as thymidine phosphoryl ase, uridine phosphorylase 1 and uridine monophosphate synthetase, reduce the sensitivity of CCA to these drugs 287,288 . The phase II enzyme glutathione S-transferase P is highly expressed in CCA, which might have an important role in inactivating drugs by conjugation with glutathione 289,290 . Changes in molecular targets could also affect the response to chemotherapy (MOC-3).…”
Section: Mechanisms Of Chemoresistancementioning
confidence: 99%
“…Thymidylate synthase has a key role in the sensitivity of CCA to 5-fluorouracil 291 . Although some controversy exists 278,288,290 , simvastatin has been shown to boost the 5-fluorouracil effect in CCA cells by suppressing thymidyl ate synthase expression 292 . Expression of ERs in CCA 93 justifies its sensitivity to tamoxifen 293 and KB9520, which activates apoptosis in experimental CCA 94 .…”
Section: Mechanisms Of Chemoresistancementioning
confidence: 99%
“…Likewise, overexpression of MRP1 (multidrug resistance-related protein-1), another protein of the ABC family of transporters, is associated with chemoresistance in primary liver tumors and consequent poor prognosis [48,49]. Consistent with this, a 2005 study of Tepsiri and colleagues that evaluated in five human CC cell lines, the expression of several genes involved in multidrug resistance, found that all of them express MRP1 [50].…”
Section: Molecular and Genetic Alterationsmentioning
confidence: 83%